Fungsi dan Peran Museum Sebagai Sumber Belajar dan Media Pelestarian Sejarah - Dahlan, Mubarak (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research was conducted to determine the function and role of museums as a medium for historical preservation. This is important because throughout its history the museum has played an important role, among others, as well as a historical tourist attraction both in cities and in a number of districts in Indonesia. The research stages of this type of library study begin with the research process of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that in the midst of the increasing number of historical learning resources through social media, the existence of museums still shows its vital role both in its physical and virtual (online) forms. Thus, the crucial issue at this time is the need to find the right strategy in utilizing museums as a medium for historical preservation. In addition, the importance of a series of socialization and promotion of museum collections, another important thing is the role of teachers and lecturers in fostering awareness of the importance of museums among students.